Past – Present – Future (?) Between the Ape Ancestor and the Artificial Intelligence - Zamojski, Adam (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
The article discusses the genesis of man, the human nature and the vision of the future of mankind. In a synthetic way it presents the main stages of the process of anthropogenesis. It describes the dual nature of modern man (biological and cultural nature). The article refers to the emergence of Artificial General Intelligence (AGI) as a challenge for humanity.